Factors affecting parliament's performance of budgetary oversight in Botswana - Marata, Keneilwe (Department of Political Studies, 2024)
Parliaments are bestowed with core functions of representation, legislation, constituency service as well as oversight and scrutiny of the executive. Parliaments are expected to perform these core functions effectively. While that is the case, the effectiveness of parliaments in doing so is often affected by several factors occurring both from inside and outside of parliament. Legislative scholarship has brought to our attention several factors and conditions affecting the effective performance of parliaments the world over. This study assesses the extent to which the parliament of Botswana has improved or weakened in selected factors affecting parliamentary performance. The selected factors assessed in this study include parliamentary capacity and resources, parliamentary autonomy and internal complexity, formal powers of parliament as well as political party dynamics. The study further assesses the extent to which the parliament of Botswana has effectively performed its budgetary oversight role as a result of its improved or weakened experience with the selected factors associated with better parliamentary performance. In its analysis, the study makes use of data from various sources including survey data from the African Legislatures Project (ALP), the Afrobarometer and Open Budget Survey (OBS) data. The study also uses data obtained through desk research and interviews. The study is divided into three sections where; Section one presents the introductory chapters 1 to 3. Section two 2 begins the analysis by assessing selected key factors associated with driving change for better performance in parliament as highlighted above. Still in Section two, the study further assesses the extent to which the parliament of Botswana has effectively performed its budgetary oversight role. In its last section (Section three), the study analyses selected key factors associated with making parliament more or less influential in its budgetary oversight role. This study establishes in its findings that the parliament of Botswana has not experienced adequate growth and improvement in the selected factors associated with driving change for better parliamentary performance. For instance, the parliament of Botswana continues to be faced with challenges of limited capacity and resources. Additionally, parliament has not improved in its autonomy and complexity. When assessing parliament's performance of budgetary oversight, the study establishes that the parliament of Botswana has not effectively performed this role. Thus, this is attributed to its (parliament's) unfavourable experience with the selected factors associated with better and improved parliamentary performance. Furthermore, the extent to which the parliament of Botswana is able to impact the budget process and thus provide effective budgetary oversight, has been attributed to other factors such as parliament's formal powers. Formal powers of the parliament of Botswana have been found to be limited. Additionally, the country's political dynamics have been found to be unfavourable towards parliament's effective performance. Drawing from the study findings and conclusions, several recommendations are made, which mostly aim at enhancing parliament's performance, especially as it pertains to its budgetary oversight role. Some of the recommendations made include the need to increase parliament's financial, human and infrastructure resources; establishing specialised offices of parliament such as the Specialised Parliamentary Budget Office; as well as enhancing parliament's committee system to ensure that parliament operates with a well-developed committee system. Other recommendations include; improving parliament's legal framework including other formal rules and processes for parliamentary budget oversight. It is also recommended for the parliament of Botswana to develop and adopt a performance assessment tool for parliament and its committees. In the end, the study suggests further research that analyses in detail the impact of even more factors on the performance of parliament beyond parliament's budgetary oversight role.